2019
DOI: 10.1136/bmjqs-2019-009775
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of a theory-based intervention to prompt front-line staff to take up the seasonal influenza vaccine

Abstract: ObjectiveTo evaluate the effectiveness of reminder letters informed by social normative theory (a type of ‘nudge theory’) on uptake of seasonal influenza vaccination by front-line hospital staff.DesignIndividually randomised controlled trial.SettingA large acute care hospital in England.ParticipantsFront-line staff employed by the hospital (n=7540) were randomly allocated to one of four reminder types in a factorial design.InterventionsThe standard letter included only general information directing the staff t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“… 51 On the other hand, using the same approach in terms of frequency and nature of reminders, an RCT in a large acute care hospital in the UK found no evidence that influenza vaccine uptake is affected by reminder letters. 52 …”
Section: Resultsmentioning
confidence: 99%
“… 51 On the other hand, using the same approach in terms of frequency and nature of reminders, an RCT in a large acute care hospital in the UK found no evidence that influenza vaccine uptake is affected by reminder letters. 52 …”
Section: Resultsmentioning
confidence: 99%
“…Embedded research teams around the world have started to systematically test the impact of using subtle changes to the way information is framed or choices are offered to nudge medical decision making 6 7. The trial by Schmidtke demonstrates the feasibility and necessity of rapid-cycle, randomised testing within a healthcare system 8. The authors randomly assigned 7540 front-line staff to either receive a standard letter reminding them of influenza vaccination or one of three letters that used insights from behavioural economics to try and better nudge healthcare workers through different ways of framing social norms.…”
mentioning
confidence: 99%
“…Just a few primary studies have been already conducted in assessing the effectiveness of nudging in promoting vaccination uptake. Some of them have described the results of nudge interventions aimed at increasing influenza vaccination uptake—although different from those that have been used in this study—with inconsistent results: some authors have described a significant increase in vaccination acceptance, while others found no effects [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 96%